2014
DOI: 10.1177/2050313x14547609
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytoclastic vasculitis in an adolescent with ulcerative colitis: Report of a case and review of the literature

Abstract: An adolescent female with long-standing, difficult-to-control ulcerative colitis developed leukocytoclastic vasculitis, a rare cutaneous extra-intestinal manifestation of the inflammatory bowel disease. The authors provide a literature review on leukocytoclastic vasculitis complicating ulcerative colitis. Furthermore, the clinical features of leukocytoclastic vasculitis are compared and contrasted with the more common cutaneous extra-intestinal manifestations of inflammatory bowel disease, erythema nodosum, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 28 publications
(69 reference statements)
0
18
0
3
Order By: Relevance
“…Butts et al reported a case of a 12-year-old girl with an acute episode of UC who developed an ecchymotic rash at the site of the intravenous catheter that was later on diagnosed as leukocytoclastic vasculitis [ 31 ]. Ho et al reported two cases of cutaneous small-vessel vasculitis in children with UC; in these cases, the IBD diagnosis should be considered only after excluding more common causes such as immunoglobulin A vasculitis, drug-induced vasculitis, or infections [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Butts et al reported a case of a 12-year-old girl with an acute episode of UC who developed an ecchymotic rash at the site of the intravenous catheter that was later on diagnosed as leukocytoclastic vasculitis [ 31 ]. Ho et al reported two cases of cutaneous small-vessel vasculitis in children with UC; in these cases, the IBD diagnosis should be considered only after excluding more common causes such as immunoglobulin A vasculitis, drug-induced vasculitis, or infections [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…). Using the keyword ‘ulcerative colitis’, 248 articles were found, of which 7 described the occurrence of LCV in the UC paediatric population . Using the keyword ‘Crohn's disease’, 266 papers were found.…”
Section: Discussionmentioning
confidence: 99%
“…All case reports concerning cutaneous lesions diagnosed as LCV at skin biopsy were included according to the EULAR/PRINTO/PRES classification criteria of childhood vasculitis . A summary of clinical features and treatment outcomes of 10 selected cases of LCV in paediatric patients with IBD is presented in Table . LCV occurs mostly in adolescents, with a striking female predominance of nearly 3:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the initial presentation is often cutaneous, LCV may cause a variety of other problems including myopathy, gastrointestinal bleeding, and renal insuffi ciency (3,4). It can also result in permanent scarring (5). Common presentations of LCV include palpable purpura, urticaria, ulcers, or nodules (3,6).…”
Section: Discussionmentioning
confidence: 99%